APLIKASI PEMILIHAN KETUA BADAN EKSEKUTIF MAHASISWA STMIK PONTIANAK BERBASIS DESKTOP - A. Murtado (SISFOTENIKA, 2011)
Abstract : The use of information technology in the voting process expected to help solving problems them. The use of computer technology in the implementation of voting is known as electronic voting. The purpose of this study was to help Badan Eksekutif Mahasiswa (BEM) STMIK Pontianak in implementing the Chief Electoral BEM with a computerized system. The research method used is descriptive method. Software design method used is RAD. Programming language used Visual Basic 6. The results of this study tested the Network Local Area Network (LAN), where several computers as a client computer and a computer unit as a data bank or as a server with a database that has been in sharingkan. With the BEM application program in STMIK Pontiaanak Based Desktop allows the user (users) the easier it is to perform the E-Voting election.Keyword : E-Voting, BEM STMIK Pontianak, RAD, Visual Basic 6